Atelir Ceremai: Identity negotiation and artists’ resistance in urban collective space - Fajar Hanif Mubarok; Tisna Prabasmoro; Lina Meilinawati Rahayu (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
This study explores the strategies of urban art collectives in shaping collective identity through collaborative practices within social spaces. Focusing on Atelir Ceremai, an art collective located on the cultural periphery of Jakarta (East Jakarta), the research examines how contemporary artists respond to marginal urban contexts through community-based artistic production. Drawing on social constructionism, collective identity theory, and theories of spatial practice, the study examines how space, language, and group dynamics shape the formation of collective consciousness among artists. This process reflects a shift from individual creativity to a communal artistic ecosystem, from market norms to symbolic autonomy, and from personal identity to a more adaptive collective identity. Based on in-depth interviews, document analysis, and participatory observation, the study finds that this transformation is made possible through various activities, including knowledge-sharing, collective use of space and tools, and the activation of joint projects. The study concludes that art collectives such as Atelir Ceremai play a crucial role in creating spaces for artistic production while simultaneously articulating adaptive forms of identity through dialectical processes. This adaptive identity is expressed through performative language, collective decision-making, and shared labor, symbolically distancing itself from the norms and logic of the art market.   Penelitian ini mengeksplorasi strategi kolektif seni urban membentuk identitas kolektif melalui praktik kolaboratif dalam ruang sosial. Dengan menyoroti Atelir Ceremai, sebuah kolektif seni yang berlokasi di pinggiran lanskap budaya Jakarta (Jakarta Timur), riset ini mengkaji bagaimana seniman kontemporer merespons konteks urban-pinggiran melalui produksi artistik berbasis komunitas. Bertolak dari kerangka konstruksionisme sosial dan teori identitas kolektif, serta teori mengenai praktik ruang, studi ini menelusuri bagaimana ruang, bahasa, dan dinamika kelompok membentuk kesadaran kolektif di antara seniman. Hal ini berkontribusi pada pergeseran dari kreativitas individual ke ekosistem artistik komunal, dari norma pasar ke otonomi simbolik, dari identitas individual ke identitas kolektif yang adaptif. Melalui wawancara mendalam, analisis dokumen, dan observasi partisipatif, ditemukan bahwa proses pergeseran tersebut dimungkinkan melalui sejumlah aktivitas yang merentang dari saling berbagi pengetahuan, ruang dan alat, serta serangkaian aktivasi proyek bersama. Penelitian ini menyimpulkan bahwa kolektif seni seperti Atelir Ceremai memainkan peran penting dalam menciptakan ruang produksi artistik sekaligus bentuk-bentuk adaptasi identitas yang terjadi secara dialektis. Identitas adaptif ini terartikulasi melalui bahasa performatif, keputusan bersama, serta kerja kolektif yang secara simbolik mengambil jarak dari norma dan logika pasar seni.